A. Boys to Girls
B. Chaperones to Students
C. Girls To Total Number Of People Attending
Answer:
19:27
4:23
1:2
Step-by-step explanation:
The number of Snickers bar and KitKat bar bought is 95 and 109 respectively.
Cost of 48 Snickers = $28
Cost per one = $28/48
= $0.583
Cost of 36 KitKat = $22.50
cost per one = $22.50/36
= $0.625
let
x + y = 204 (1)
0.583x + 0.625y = 123.50 (2)
From (1)
x = 204 - y
substitute into (2)
0.583x + 0.625y = 123.50
0.583(204 - y) + 0.625y = 123.50
118.932 - 0.583y + 0.625y = 123.50
- 0.583y + 0.625y = 123.50 - 118.932
0.042y = 4.568
y = 4.568/0.042
y = 108.761904761904
Approximately,
y = 109
substitute into (1)
x + y = 204
x + 109 = 204
x = 204 - 109
x = 95
Learn more about equation:
Answer: 96 snickers and 108 kitkats
Step-by-step explanation: you should do system of equations and then it would be 48s+36k=204 and 28s+22.5k=123.5, after you do the math, the answer turns out to be 96 snickers and 108 kitkats. :)
Let the number be x.
4x - 8 =12
4x =12 +8 ( you bring the eight over to the 12, it becomes positive )
4x = 20
x = 20÷4
x = 5
The problem is a basic algebra equation. It translates to 4x - 8 = 12, which can be solved by adding 8 to both sides and then dividing by 4 to get x=5. The answer is 5.
The subject of this question is Mathematics, specifically algebra. To solve this equation, start by translating the problem into a mathematical expression. This can be done as follows: 4 times a number is represented as 4x, then decreased by eight is -8 and the equation equals twelve (12).
Therefore, the equation is 4x - 8 = 12. To solve for x, you can start by adding 8 to both sides of the equation obtaining 4x = 20. Lastly, divide both sides by 4 to find x, which gives x = 5.
Therefore, the number that meets the condition '4 times a number, decreased by 8 equals 12' is 5.
#SPJ2
Answer:
( f o g) (x) = 3x²+5
Step-by-step explanation:
We have given two functions :
f (x) = 3x + 2
g(x) = x² + 1
We have to find ( f o g) (x) =?
( f o g) (x) = (f(g(x))
Putting the values of functions in above formula.
( f o g) (x) = 3(x²+1)+2
( f o g) (x) = 3x²+3+2
Adding like terms,we have
( f o g) (x) = 3x²+5
( f o g) (x) = 3x²+5 is the answer.
Answer: (f o g)(x)=
Step-by-step explanation:
To solve this problem you must apply the following proccedure:
(f o g)(x) indicates that you must substitute the function g(x) into the function f(x).
Therefore, you have:
(f o g)(x)=
Now, you must simplify it, as it is shown below:
Apply the distributive property and add the like terms:
(f o g)(x)=
(f o g)(x)=